ANATOMICAL AND FUNCTIONAL CONNECTIONS BETWEEN THE LOCUS COERULEUS AND THE NUCLEUS TRACTUS SOLITARIUS IN NEONATAL RATS - Lopes, L. T. [UNESP] (2016)
This study was designed to investigate brain connections among chemosensitive areas in newborn rats. Rhodamine beads were injected unilaterally into the locus coeruleus (LC) or into the caudal part of the nucleus tractus solitarius (cNTS) in Sprague-Dawley rat pups (P7-P10). Rhodamine-labeled neurons were patched in brainstem slices to study their electrophysiological responses to hypercapnia and to determine if chemosensitive neurons are communicating between LC and cNTS regions. After 7-10 days, retrograde labeling was observed in numerous areas of the brainstem, including many chemosensitive regions, such as the contralateral LC, cNTS and medullary raphe. Whole-cell patch clamp was done in cNTS. In 4 of 5 retrogradely labeled cNTS neurons that projected to the LC, firing rate increased in response to hypercapnic acidosis (15% CO2), even in synaptic blockade medium (SNB) (high Mg2+/lowCa(2+)). In contrast, 2 of 3 retrogradely labeled LC neurons that projected to cNTS had reduced firing rate in response to hypercapnic acidosis, both in the presence and absence of SNB. Extensive anatomical connections among chemosensitive brainstem regions in newborn rats were found and at least for the LC and cNTS, the connections involve some CO2-sensitive neurons. Such anatomical and functional coupling suggests a complex central respiratory control network, such as seen in adult rats, is already largely present in neonatal rats by at least day P7-P10. Since the NTS and the LC play a major role in memory consolidation, our results may also contribute to the understanding of the development of memory consolidation. (C) 2016 IBRO. Published by Elsevier Ltd. All rights reserved.